AKIBAT HUKUM PERJANJIAN ARISAN DITINJAU DARI ASPEK HUKUM PERDATA - KHOSI'AH KHOSI'AH (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT Man is a social being, always interact with each other in an effort to achieve prosperity of life. One form of interaction is Arisan. As an activity in society, Arisan is a concept that can not be separated in the territory of civil law arrangement. Implementation of  the concept of Arisan by the community not infrequently has caused various problem, thus demanding a solution that can meet the sense of society and state. The settlement has been answered by law that has divided its authority in areas differentiated by the type of problem arising. Arisan activity is a form of application of certain law (cicvil) which then raises various problem. In its journey it is often found that the solution of the problem is beyond the proper field of law. Therefore, the research conducted with normative juridical method using the approach of law and concept approach on Arisan, his position in the law of engagement, as well as the legal consequences in relation to the legal steps to be taken to resolve the problems arising. The results of the study are written in the thesis as a result of Arisan Law law in Terms of Civil Law.Keywords: Arisan, consequence, effort, solution, problem.